PRINCIPLES OF JUSTICE AND LEGAL CERTAINTY IN CRIMINAL LAW ENFORCEMENT IN INDONESIA - Lury Elza Alex; Lies Sulistiani (Awang Long Law Review, 2026)
This research analyses the conceptual conflict between legal certainty and justice within Indonesia's criminal law system, especially with recent advancements like restorative justice and judicial discretion. Legal certainty prioritizes the uniform application of formal legal principles, while justice requires contextual interpretation to reflect social reality. This conflict often leads to discrepancies in court rulings and undermines the credibility of law enforcement. This study utilizes a normative legal approach via legislative, conceptual, and case analysis. This research combines doctrinal legal sources with theoretical frameworks to examine the reconciliation of legal certainty and justice within the criminal justice system. Special emphasis is placed on judicial procedures, such as discretionary judgments and judicial pardons, as mechanisms that connect formal legality with actual justice. The results suggest that achieving harmony between legal certainty and justice requires an integrative framework that encompasses both positive law and the principles of living law, rather than relying only on a strict normative approach. These principles include restorative practices, social reconciliation, proportionality in punishment, and community-based conflict resolution processes grounded in Indonesian legal tradition. This work introduces a Normative Integrative Harmonization Model that regards legal certainty and fairness as complimentary concepts rather than opposing ones. The paradigm highlights three fundamental components: (1) organized judicial discretion informed by accountability criteria, (2) rechtsvinding as a contextual interpretive tool, and (3) the incorporation of living law principles into formal legal systems. This model advances the evolution of responsive criminal law theory and provides a conceptual basis for enhancing consistency, equity, and legitimacy within Indonesia's criminal justice system.